Popular knowledge of the mammals of Barra Honda National Park, Nicoya, Costa Rica - Castillo-Chinchilla, Maikol (2018)
Human activities and loss of habitat can have negative effects on flora and fauna. It has been shown that the study of popular knowledge of faunal groups represents a valuable resource for decision making. The objective of this study is to carry out an analysis of popular knowledge about terrestrial mammals in six villages surrounding Barra Honda National Park, Nicoya (BHNP), Costa Rica. The analysis of survey results was carried out taking into account the frequencies and percentages obtained in relation to popular knowledge, species diversity, perceptions on terrestrial mammals and hunting activities. Interviewees mentioned that in areas outside the BHNP, 14 to 18 species of mammals can be observed, including puma (Puma concolor), tolomuco (Eira barbara), tepezcuintle (Cuniculus paca) and white-tailed deer (Odocoileus virginianus). About 50% of respondents identified tepezcuintle and white-tailed deer as the species that are most frequently hunted. Some of the mammals identified by the villagers in the areas surrounding the BHNP are regarded as harmful to crops, farm animals and cattle, and are hunted indiscriminately.